Revisiting Public Support for the Euro, 1999–2017: Accounting for the Crisis and the Recovery. (12th July 2019) - Roth, Felix; Baake, Edgar; Jonung, Lars; Nowak‐Lehmann D., Felicitas
Abstract: This article explores the evolution and determinants of public support for the euro since its creation in 1999 until the end of 2017, thereby covering the pre‐crisis experience of the euro, the crisis years and the recent recovery. Using uniquely large macro and micro databases and applying up‐to‐date econometric techniques, the authors revisit the growing literature on public support for the euro. First, we find that a majority of citizens support the euro in nearly all 19 euro area member states. Second, we offer fresh evidence that economic factors are important determinants of change in the level of support for the euro: crisis reduces support while periods of recovery from unemployment bode well for public support. This result holds for both macroeconomic and microeconomic factors. Turning to a broad set of socioeconomic variables, we find clear differences in support due to education and perceptions of economic status.